Secrecy in US foreign policy Nixon, Kissinger and the rapprochement with China - Komine, Yukinori (Ashgate Pub., 2008)
Examines the pursuit of secrecy by President Nixon and National Security Advisor Kissinger in foreign policy decision-making as a principle characteristic of the US rapprochement with China. This book sheds light on the evolution of China initiatives and demonstrates the existence of policy options and different perspectives among US officials.